Pengaruh job satisfaction terhadap employee performance melalui work engagement pada karyawan - Nabila, Vera; Budiono, (Jurnal Ilmu Manajemen, 2025)
PT. XYZ is a company engaged in the field of construction, which also provide services such as spool fabrication, valve overhaul, valve actuator, heat exchange and cooling unit as well as the manufacture of electrical panels and preparation of Mesoscale Convective Complex (MCC) for nitrogen factory. PT. XYZ also serves various international oil companies. This study aims to analyze the influence of job satisfaction on employee performance through work engagement at PT. XYZ. This research uses quantitative methods. Non-probability sampling with a saturated sample technique was employed, where the entire population is sampled with 67 respondents. The statistical analysis used in this research is the Structural Equation Model - Partial Least Square (SEM-PLS) with SmartPLS 3.0 software. The results of this research explain that job satisfaction has a positive and significant effect on employee performance. Job satisfaction has a positive and significant effect on work engagement. Work engagement has a positive and significant impact on employee performance. The analysis of the indirect influence of work engagement is able to mediate the effect of job satisfaction on employee performance. This study emphasizes the practical implications of ensuring employee job satisfaction that companies should be able to fulfill, as it can increase employee enthusiasm, feelings of happiness when carrying out work, and work engagement, so that employee performance will also always increase.